Academic Anxiety of LPTK Students: A Predictor Analysis in AI-Based Scientific Writing - Rizki Mustikasari; Ratri Harida; Cutiana Windri Astuti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze the influence of emotion regulation and self-efficacy on academic anxiety, with motivation as a moderating variable, among students majoring in education in Ponorogo Regency. This study uses a correlational, ex post facto, quantitative approach.  A total of 370 respondents who were writing scientific papers were involved. This study employed a validated and reliable questionnaire. Path analysis reveals that emotion regulation has a strong and significant impact on reducing academic anxiety, both directly and through its influence on motivation, whereas self-efficacy has a relatively weak influence. These results confirm that emotional management skills, such as cognitive reappraisal and expression control, are key factors in reducing psychological stress in students during the scientific writing process. Theoretically, these findings support the notion that emotion regulation is a crucial determinant of academic success. Yet, it also practically provides implications for higher education to design interventions based on emotion regulation and motivation enhancement to reduce students' academic anxiety. The results of the study can serve as the basis for a predictive relationship study of the variables.